A luminescent benzothiadiazole-bridging bis(salicylaldiminato)zinc(ii) complex with mechanochromic and organogelation properties. Issue 17 (18th April 2018) - Song, Xiaoxian; Yu, Hanbo; Yan, Xianju; Zhang, Yuewei; Miao, Yang; Ye, Kaiqi; Wang, Yue
Abstract : Herein, a new bis(salicylaldiminato)Zn(ii ) Schiff base complex, BTZn, derived from benzo[ c ][1, 2, 5]thiadiazole-5, 6-diamine was designed and synthesized. Abstract : Herein, a new bis(salicylaldiminato)Zn(ii ) Schiff base complex, BTZn, derived from benzo[ c ][1, 2, 5]thiadiazole-5, 6-diamine was designed and synthesized. It exhibited unique mechanical force-induced luminescence change characteristic. Upon mechanical grinding, the as-prepared BTZn solid crystalized from an ethanol/dichloromethane solution displays a high-contrast emission-colour variation from yellow (emission maximum λ em = 545 nm) to red ( λ em = 645 nm), and this emission variation can be erased through solvent vapour treatment. The reversible emission colour alteration between yellow and red can be repeatedly performed. Thermal annealing of the as-prepared BTZn solid resulted in a more ordered orange phase with an emission maximum of 575 nm. The multi-stimuli-responsive luminescence mechanism has been investigated via SEM, powder X-ray diffraction (XRD), and thermal analyses. It is demonstrated that mechanical force can induce morphology transformation from the crystalline to the amorphous phase, which is accompanied by a change in the BTZn molecular packing modes. The BTZn-based solids have molecular packing-dependent emission characteristics. The XRD experimental results reveal that for the yellow emissive as-prepared BTZn solid, a columnar square molecular arrangement is adopted. On the other hand, the BTZn complex exhibits the ability to organize into organic luminescent gels constructed by one-dimensional BTZn molecular nanofibrils. The BTZn xerogel also displays mechanochromic properties. Accordingly, BTZn-based solids may be potential candidates for the development of new stimuli-responsive materials.